The status of diabetes control in Malaysia: results of DiabCare 2008 - Mafauzy, Mohamed; Hussein, Z.; Chan, Siew Pheng (Malaysian Medical Association, 2011)
DiabCare Malaysia 2008 evaluated the current status of diabetes care in Malaysia as a continuation of similar cross-sectional studies conducted previously in 1997, 1998, 2001 and 2003. The current study recruited 1670 patients from general hospitals, diabetes clinics and referral clinics to study current scenario of diabetes management. We report the results of type 2 diabetic population who constituted 92.8% (n = 1549). Results showed deteriorating glycaemic control with mean HbA1c of 8.66 +/- 2.09% with only 22% of the patients achieving ADA target of < 7%. 80.3% of patients were hypertensive and 75% were on anti-hypertensive medication. 46% of patients had LDL levels > 2.6 mmol/L; 19.8% had triglycerides > 2.2 mmol/L; 27.4% had HDL < 1 mmol/L despite 85% of the patients being on lipid lowering agents. Microvascular, macrovascular and severe late complications were reported in 75%, 28.9% and 25.4% patients respectively. The rates of diabetic complications were cataract 27.2%, microalbuminuria 7%, neuropathy symptoms 45.9%, leg amputation 3.8% and history of angina pectoris was 18.4%. Quality of life evaluation showed that about one third of patients have poor quality of life. Also, there was poor adherence to diet, exercise and self testing of blood glucose. In conclusion, majority of the patients were still not satisfactorily controlled. There is an urgent need for effective remedial measures to increase adherence to practice guidelines and to educate both patients and healthcare personnel on importance of achieving clinical targets for metabolic control.